Overexpression of lily MicroRNA156-resistant SPL13A stimulates stem elongation and flowering in Lilium formosanum under non-inductive (non-chilling) conditions - Yamagishi, Masumi; Nomizu, Toshikazu; Nakatsuka, Takashi (Frontiers in Plant Science, 2024)
Flowering plants undergo juvenile vegetative, adult vegetative, and reproductive phases. Lily plants (Lilium spp.) develop scaly leaves during their juvenile vegetative phase. Stem elongation occurs in the adult vegetative phase and is followed by floral transition. As the duration of the juvenile vegetative phase is long in lilies, the microRNA156 (miR156) and SQUAMOSA PROMOTER-BINDING PROTEIN-LIKE (SPL) modules are expected to play a major role in vegetative phase change and flower induction. In the present study, we aimed to explore the functions of lily SLP13A. We evaluated phenotypic changes and gene expression in L. formosanum plants overexpressing miR156-resistant SPL13A (rSPL13A) and examined the accumulation levels of gene transcripts and mature miRNAs in non-transformed L. longiflorum plants. Lily plants overexpressing rSPL13A exhibited stem elongation under non-inductive conditions, and FLOWERING LOCUS T (FT) genes were poorly involved in this stem elongation. Flowering was induced in the transformed plants with elongated stems, and the accumulation of MADS5 (APETALA1) transcripts and mature miR172 was elevated in these plants. In non-transformed lilies, SPL13A transcripts were highly accumulated in the shoot apices of both juvenile and adult plants. As mature miR156 was poorly accumulated in the shoot apices of the adult plants, SPL13A was active enough to stimulate stem elongation and flower induction. In contrast, mature miR156 was reliably detected in shoot apices of the juvenile plants. Because our transient assay using tobacco plants expressing a SPL13A-GFP fusion protein indicated that miR156 repressed SPL13A expression mainly at the translational level, SPL13A activity should be insufficient to stimulate stem elongation in the juvenile plants. In addition, the accumulation of MADS5 transcripts and mature miR172 in the shoot apices increased with plant growth and peaked before the transition to the reproductive phase. Therefore, we conclude that SPL13A regulates stem elongation in the adult vegetative phase, which differs from the mechanisms evaluated in Arabidopsis and rice, wherein stem elongation proceeds in a reproductive phase and FT genes are heavily involved in it, and that SPL13A induces flowering by the activation of genes related to the age pathway underlying floral transition, as APETALA1 and primary-MIR172 are mainly involved in this pathway.